Genotyping of the Pseudorabies Virus by Multiplex PCR Followed by Restriction Enzyme Analysis. (24th November 2011) - Fonseca, Antônio Augusto; Magalhães, Cristina Gonçalves; Sales, Érica Bravo; D'Ambros, Régia Maria; Ciacci-Zanella, Janice; Heinemann, Marcos Bryan; Leite, Rômulo Cerqueira; Reis, Jenner Karlisson Pimenta dos
Abstract : Suid herpesvirus 1 (SuHV-1) is the causative agent of Aujeszky's disease. The infectious agent has only one serotype, but it was classified by restriction enzyme analysis of the whole genome into four genotypes, named I to IV. The aim of this study was to standardize a rapid method for genotyping SuHV-1 without virus isolation, using a multiplex-PCR followed by enzymatic restriction analysis. The complete genome of the virus was analyzed in silico to determine the restriction sites for the enzyme BamH I. Primers were designed to flank sites with emphasis on certain points of differentiation of genotypes. The standard PCRs were able to detect the SuHV-1 and also to differentiate genotypes from brain tissue of infected pigs. The BamH I-PCR is a rapid, practical, and sensitive way to genotype SuHV-1.